2016
DOI: 10.1590/1983-40632016v4641587
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contents in Latosols cultivated with vegetable crops1

Abstract: Heavy metals are naturally found in soils, but their levels may increase as a result of anthropogenic actions. This study aimed at determining the concentrations of Cd, Cu, Mn, Ni, Pb and Zn in Yellow Latosol from vegetable crops areas, as well as the influence of the cultivation and position in the landscape on the accumulation of these elements. Soil samples were collected from five farming areas and four areas with natural vegetation, which served as a reference. Soil was collected along the planting rows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
2
25
1
3
Order By: Relevance
“…Soils from forest areas have a higher OM content, which is in accordance with several studies that compare changes in soil chemical attributes attributed to agricultural practices in comparison to natural areas (Portugal et al, 2010;Silva et al, 2016). The highest OM contents in native vegetation areas are explained by the greater contribution of organic residues (Portugal et al, 2010) since the anthropic interference, such as the use of agricultural implements and cultural practices, accelerates OM degradation (Freitas et al, 2015).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Soils from forest areas have a higher OM content, which is in accordance with several studies that compare changes in soil chemical attributes attributed to agricultural practices in comparison to natural areas (Portugal et al, 2010;Silva et al, 2016). The highest OM contents in native vegetation areas are explained by the greater contribution of organic residues (Portugal et al, 2010) since the anthropic interference, such as the use of agricultural implements and cultural practices, accelerates OM degradation (Freitas et al, 2015).…”
Section: Resultssupporting
confidence: 87%
“…By means of the factor and principal components analyses, Coletti et al (2010) concluded that substances of ammonia, ammoniacal nitrogen, and nitrate from agricultural activities were the main contaminants of water resources. In the study of Silva et al (2016), the application of these analyses not only discriminated the enrichment sources of OM, P, and heavy metals in vegetable cultivation but also elected and revealed the decisive factor for distributing these variables along the hillside of an Oxisol. In short, multivariate statistics allows a greater capacity to describe intra-and interdependence relationships in agricultural systems, allowing establishing and planning more appropriate management practices.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide increase in anthropogenic, industrial and agricultural activities is responsible for the growing release of different pollutants into the environment (KABATA-PENDIAS, 2010;MACEDO et al, 2012;SILVA et al, 2016). Heavy metals such as cadmium (Cd), copper (Cu), manganese (Mn), nickel (Ni), zinc (Zn) and lead (Pb) are the most well-known and cause significant damage to the environment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals such as cadmium (Cd), copper (Cu), manganese (Mn), nickel (Ni), zinc (Zn) and lead (Pb) are the most well-known and cause significant damage to the environment and human health. Farming in soils that are subject to intensive fertilizer and pesticide application and poor quality irrigation water (SILVA et al, 2016) are the main entry routes for these metals into human and animal diets (CHANEY;OLIVER, 1996;FERNANDES et al, 2007;CONAMA, 2009;ATSDR, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation